Strengthening the Resilience of an Economy. Strategies to Prevent another Crisis - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2009)
The financial crisis has affected the real economy in stages yet nevertheless at an unexpected rate and with all regions being affected simultaneously. It advanced almost independently of the regions' exposure to the actual initial causes, among them the subprime crisis, innovative financial products, dubious microeconomic incentives, inefficient regulation and macroeconomic imbalances. The following analysis poses the question how the national economic structures can be made more resilient to a shock (be it a financial crisis or any other form of shock) and how economic policy can act in order to stabilise the economy before and after such a shock. This analysis supplements studies on the causes of the financial crisis, proper macroeconomic responses to the crisis and regulatory reforms on a national and international level. It enlarges the list of the traditional instruments of economic stabilisation policy by combining them with structural policies. Measures in five policy areas which could be the key to more effectively preventing a further crisis are discussed. However, a resilient economy is not in itself a political goal; it is only a necessary condition for a successful growth and employment policy. Furthermore, economic policy to increase resilience against shocks should not contain any protectionist elements since these lead to losses in income and employment levels.
Keywords: 330; financial crisis; business cycle; stabilisation policy; resilience; Finanzkrise; Internationaler Finanzmarkt; Konjunktur; Wirtschaftliche Anpassung; Regulierung; Finanzmarktregulierung; Österreich; Welt